Contextual reinterpretation of quantum nonlocality - Khrennikov, Andrei 1958- (Cambridge University Press, 2024)
The quantum information revolution has had a huge impact not only on quantum technologies, including quantum computing and cryptography, but also on the foundations of quantum mechanics. This book presents the information viewpoint on the foundations of quantum physics by highlighting the role of complementarity and contextuality and coupling the ideas of the fathers of quantum mechanics, Bohr and Einstein, with the modern quantum information framework. The classical-quantum dilemma is resolved through an appeal to the Bild conception of scientific theories established in the 19th century by Hertz and Boltzmann. Bell inequalities are treated from the complementarity-contextuality viewpoint, supporting the attempts to discard nonlocality from quantum physics. Philosophical aspects of the topic are explored from a physicist's perspective, balancing accessibility with scientific rigour. This unique approach to quantum foundations will be of interest to graduates, Ph.D. students and researchers in fields ranging from quantum information to philosophy